Applications of Novel Drug Delivery Systems for Enhancement Bioavailability of Antiretrovirals with Special Focus on Nanotechnology - Kumar, Dr. S. Sathesh (Asian Journal of Pharmaceutics (AJP), 2022)
Antiretroviral (ARV) therapy is a chemotherapeutic approach to treat viral infections such as AIDS. Remarkable therapeutic strategies improved the mortality rate in HIV patients. However, the neurocognitive disorders associated with HIV is not helmed properly due to the tight blood-brain barrier that restricts majority of ARVs to enter the brain parenchyma through the cerebral capillary endothelium. Conventional formulations are not adequate to reach these needs in the ARV therapy. Moreover, careful monitoring of pharmacokinetic parameters of the ARV drugs is important to achieve utmost therapeutic efficiency. However, the majority of the drugs are confronting this issue due to their poor aqueous solubility and inappropriate tissue permeability. Diversified nanotechnological and varied accustomed approaches were impended using novel polymers (both natural and synthetic) to ameliorate these pharmacokinetic constraints. Ample literature is available about the nanotechnological approaches allude to the development in the field for the enhancement of oral bioavailability, potency with less side effects. Nanotechnological cherishment also helps to control drug resistance and drug abuse. Making sub-micron level drug particles of poor water-soluble ARV drugs revamp the oral bioavailability by amplified surface area, improved interfacial tension at drug and solvent interface. The permeability issues are abolished by tailoring physical structure of the drug particle. Stability in the gastric environment, bypassing the early hepatic metabolism of ARV drugs also can be conquered with nanotechnological contrivances. Among all, nanocarrier, nano vesicular drug delivery system are well-crammed techniques. This review enumerates a detailed picture of bioavailability enhancement techniques for ARV drugs through nanotechnological advents.